NACLIM - Fluxes: Denmark Strait overflow transport - Detlef Quadfasel; Kerstin Juchumsen (Zenodo, 2015)
Description: Daily average of overflow transport on Denmark Strait Period: September 1996 – September 2014 Location: 66° N 28° W (map) Instruments: Moored ADCPs Variables: Overflow volume transport. Updated on : 18 December, 2014 Reference: http://naclim.zmaw.de/fileadmin/user_upload/naclim/Data/CT2datasets/pre_naclim_dataset/Denmark_Strait/Jochumsenetal_JGR2012.pdf